The Notebook of Kamāl al-Dīn the Weaver Aleppine notes from the end of the 16th century - Liebrenz, Boris; Richardson, Kristina L. (Bibliotheca Islamica, 2023)
Only a fragment of the sizeable work of Kamāl al-Dīn survived and is now preserved in the Forschungsbibliothek Schloss Friedenstein in Gotha. It represents the earliest known Arabic notebook of an artisan or merchant and sheds light on the everyday life in 10th/16th century Aleppo.